Comparative Analysis the Complete Chloroplast Genomes of Nine Musa Species: Genomic Features, Comparative Analysis, and Phylogenetic Implications - Song, Weicai; Ji, Chuxuan; Chen, Zimeng; Cai, Haohong; Wu, Xiaomeng; Shi, Chao; Wang, Shuo (Frontiers in Plant Science, 2022)
Musa (family Musaceae) is monocotyledonous plants in order Zingiberales, which grows in tropical and subtropical regions. It is one of the most important tropical fruit trees in the world. Herein, we used next-generation sequencing technology to assemble and perform in-depth analysis of the chloroplast genome of nine new Musa plants for the first time, including genome structure, GC content, repeat structure, codon usage, nucleotide diversity and etc. The entire length of the Musa chloroplast genome ranged from 167,975 bp to 172,653 bp, including 113 distinct genes comprising 79 protein-coding genes, 30 transfer RNA (tRNA) genes and four ribosomal RNA (rRNA) genes. In comparative analysis, we found that the contraction and expansion of the inverted repeat (IR) regions resulted in the doubling of the rps19 gene. The several non-coding sites (psbI–atpA, atpH–atpI, rpoB–petN, psbM–psbD, ndhf–rpl32 and ndhG–ndhI) and three genes (ycf1, ycf2 and accD) showed significant variation, indicating that they have the potential of molecular markers. Phylogenetic analysis based on the complete chloroplast genome and coding sequences of 77 protein-coding genes confirmed that Musa can be mainly divided into two groups. These genomic sequences provide molecular foundation for the development and utilization of Musa plants resources. This result may contribute to the understanding of the evolution pattern, phylogenetic relationships as well as classification of Musa plants.